Mutations in the MECP2 Gene Are Not a Major Cause of Rett Syndrome-Like or Related Neurodevelopmental Phenotype in Male Patients - Santos, M (2016)
Rett syndrome is a genetic neurodevelopmental disorder that affects mainly girls, but mutations in the causative MECP2 gene have also been identified in boys with classic Rett syndrome and Rett syndrome-like phenotypes. We have studied a group of 28 boys with a neurodevelopmental disorder, 13 of which with a Rett syndrome-like phenotype; the patients had diverse clinical presentations that included perturbations of the autistic spectrum, microcephaly, mental retardation, manual stereotypies, and epilepsy. We analyzed the complete coding region of the MECP2 gene, including the detection of large rearrangements, and we did not detect any pathogenic mutations in the MECP2 gene in these patients, in whom the genetic basis of disease remained unidentified. Thus, additional genes should be screened in this group of patients.